Fontaine-André. Les 850 ans de l'abbaye. Une source non tarie - Chambet, Claude-Pierre (L'Express, 1993)
Keywords: fontaine-andré

Santa Radegundis - Cruz, V. de la (Diario de Burgos, 1993)
Keywords: sordillos

Mare de Déu de Bonrepòs - Adell i Gisbert, Joan-Albert; Pladevall i Font, Antoni; Puigferrat i Oliva, Carlos (Catalunya romànica: Pallars Sobirà, Pallars Jussà., 1993)
Keywords: bonrepòs

Abbayes, prieurés et monastères de l'ordre de Prémontré en France des origines à nos jours: dictionnaire historique et bibliographique - Ardura, Bernard (Presses universitaires de Nancy; Centre culturel des Prémontrés, 1993)
OCLC: 36393383
Keywords: 🇫🇷 france (general)

Prémontrés en Bohème, Moravie et Slovaquie - Ardura, Bernard; Dolista, Karel; Lorencová, Jarmila (Karolinum, 1993)
Keywords: 🇨🇿 czechia (general); 🇸🇰 slovakia (general)

Goederenverwerving en goederenbeheer van de abdij Mariënweerd (1129-1592) - Bavel, Bas J. P. van (Uitgeverij Verloren, 1993)
Google-Books-ID: t5hDP42vsMgC
Keywords: mariënweerd

Stichtingsplaats, ontginning en goederenverwerving. De economische ontwikkeling van Norbertijner abdijen in de Nederlanden (12de-13de eeuw) - Bavel, Bas J.P. van (Ideaal en werkelijkheid : stichtingsplaatsen en ontginningactiviteiten van Premonstratenzers in de Nederlanden : verslagen van de derde contactdag Abdij van Tongerlo, zaterdag 15 mei 1993, 1993)
Keywords: 🇳🇱 netherlands (general)

L'abbaye Sainte-Marie de Blanchland - Bindel, Robert (Actes Officiels du 18e Colloque du C.E.R.P., 1993)
Keywords: blanchland

Letopis milevského opata Jarlocha a jeho pramenná hodnota - Bláhová, Marie (Ceský stát na prelomu 12. a 13. století, 1993)
[Die Chronik des Abtes Jarloch von Mühlhausen und ihr Quellenwert. ]
Keywords: milevsko

The Premonstratensian Order: a preliminary survey of its growth and distribution in Medieval Europe - Bond, C.J. (In Search of Cult: Archaeological Investigations in Honour of Philip Rahtz, 1993)
Keywords: 📚 premonstratensian (general)

850 Jahre Prämonstratenserabtei Windberg - Chrobak, Werner Johann; Handgrätinger, Thomas; Mai, Paul; Bosl, Karl (Schnell & Steiner, 1993)
OCLC: 505716330
Keywords: windberg

Das Prämonstratenserkloster Mildenfurth - Eichhorn, Herbert (Verlag Ausbildung + Wissen, 1993)
Keywords: mildenfurth

Zur Bedeutung des Prämonstratenserordens für Mildenfurth - Eichhorn, Herbert (Der Landkreis Gera, 1993)
Keywords: mildenfurth

Seminaret "Kloster og by" 11.-13. november 1992: omkring Olavsklosteret, Premonstratenserordenen og klostervesenet i middelalderen - Eriksson, Jan E. G.; Schei, Kari (Tønsberg Bibliotek og Riksantikvaren, Utgravningskontoret for Tønsberg, 1993)
OCLC: 467278997
Keywords: tønsberg

Die Abtei Bellapais : ein Führer durch Geschichte und Bauwerk - Fiene, Eckart (E. Fiene, 1993)
Keywords: bellapais

La necropole de l'abbaye Notre-Dame-de-Lieu-Restaure, Bonneuil-en-Valois, Oise - François, Jean-Luc (Moines et moniales face à la mort. Actes du colloque de Lille, 2-4 octobre 1992, 1993)
Keywords: lieu-restauré

Die Pfarrer zu Gründau auf dem Berg 1340–1600 - Frickel, Jürgen H. (Hessische Familienkunde, 1993)
Keywords: niedergründau

Kaiser Heinrich IV. stiftete Königskamp für Katharinenkloster. Vor 800 Jahren gegründet und „in Gottes Gnade“ zu Reichtum gelangt - Fritzsch, Walter (Heimat Dortmund: Stadtgeschichte in Bildern und Berichten, 1993)
Keywords: dortmund

Norberto reis naar Laon, Kamerijk en Njvel en de inbezitneming van Prémontré, 1120 - Grauwen, Wilfrid (Analecta Praemonstratensia, 1993)
Keywords: 👤 norbert of xanten

De duivelverhalen en het exorcisme van Norbert te Maastricht, 1122 - Grauwen, Wilfried Marcel (Analecta Praemonstratensia, 1993)
Keywords: 👤 norbert of xanten

Hoe Norbert de H. Schrift navolgde - Grauwen, Wilfried Marcel (Analecta Praemonstratensia, 1993)
Keywords: 👤 norbert of xanten

Norbert et de concilies van Keulen en Fritzlar - Grauwen, Wilfried Marcel (Analecta Praemonstratensia, 1993)
Keywords: 👤 norbert of xanten

Norbert predikt te Antwerpen in 1124 - Grauwen, Wilfried Marcel (Analecta Praemonstratensia, 1993)
Keywords: 👤 norbert of xanten

Norberts reis naar Laon, Kamerijk en Nijvel en de inbezitneming van Prémontré, 1120 - Grauwen, Wilfried Marcel (Analecta Praemonstratensia, 1993)
Keywords: 👤 norbert of xanten

Das Kloster Maria zum Weiher vor Köln (1198-1474) und sein Fortleben in St. Cäcilien bis zur Säkularisation - Gückel, Irene (Janus, 1993)
Keywords: cologne (weiher)

800 Jahre Kloster Mildenfurth - Heller, Paul (Heimatbote Greiz, 1993)
Keywords: mildenfurth

Voormalige Norbertinessenpriorij Leliëndaal te Hombeek - Herck, K. van (Handelingen (Mechelen), 1993)
Keywords: leliëndaal

Aspectos estilisticos y formales de la escultura tardorromanica del monasterio de Santa Maria la Real en Aguilar de Campoo (Palencia). Fuentes de inspiracion e irradiacion de modelos - Hernando Garrido, José Luis (Universidat Autónoma de Barcelona, 1993)
Keywords: aguilar de campoo

Die Kirche St. Jakob in Klosters 1493-1993. 500 Jahre nach dem Chorbau - Hitz, Florian; Kasper-Kuoni, Maria (1993)
Keywords: prättigau

Die Einnahmen der Abtei Hamborn (ca. 1500 - ca. 1584) aus Holten, Walsum, Götterswickerhamm, Spellen, Borth, Ginderich, Wesel, Hünxe, Dinslaken und Orsoy, als Manuskript hg. - Horstkötter, Ludger (Abtei Hamborn, 1993)
Keywords: hamborn

Dokumente zu den inneren Verhältnissen der Abtei Hamborn (1396 - 1806), vorwiegend aus Beständen des Hauptstaatsarchivs Düsseldorf - Horstkötter, Ludger (Abtei Hamborn, 1993)
Keywords: hamborn

Křtiny : Poutní kostel Jména Panny Marie - Horyna, Mojmír; Prnka, Tomáš (Historická společnost Starý Velehrad, 1993)
Keywords: křtiny

Bischof Heinrich Zdik († 1150) - ein Prämonstratenser? - Huber, Kurt A. (Archiv für Kirchengeschichte von Böhmen, Mähren, Schlesien, 1993)
Place: Bad Schussenried Publisher: Gerhard Hess Verlag ; Königstein, Taunus : Institut für Kirchengeschichte von Böhmen-Mähren-Schlesien, 1967-
Keywords: 📚 premonstratensian (general)

Das Kloster Rüti: eine Begräbnisstätte des ostschweizerischen Adels - Illi, Martin (Eine Ahnung von den Ahnen : archäologische Entdeckungsreise ins Zürcher Oberland, 1993)
Keywords: rüti

Die Stiftskirche Keppel als nassauische Grablege im 15. Jahrhundert - Isenberg, Erwin (Heimatjahrbuch für den Lahn-Dill-Kreis, 1993)
Keywords: keppel

Ein Beitrag zur Chronistik des altnassauischen Stiftes Keppel - Isenberg, Erwin (Heimatjahrbuch für den Lahn-Dill-Kreis, 1993)
Keywords: keppel

Kalendarz opactwa sw. Wincentego we Wroclawiu - Jasinski, Kazimierz (Kultura sredniowieczna slaska: pierwiastki rodzime i obce, 1993)
Keywords: wrocław

Stellarum Dominae stallatum templum: Ein Beitrag zur Ikonologie der Prämonstratenserabteikirche in Windberg - Kaiser, Alfred (850 Jahre Prämonstratenserabtei Windberg, 1993)
Keywords: windberg

Dragsmarks kloster - Kjellgren, Barbara (Bohuslän, 1993)
Keywords: dragsmark

Das Ordensrecht der Prämonstratenser vom späten 12. Jahrhundert bis zum Jahr 1227. Der „Liber consuetudinum“ und die Dekrete des Generalkapitels - Krings, Bruno (Analecta Praemonstratensia, 1993)
Keywords: ⚖️ chapters and statutes

La lettera di Anselmo di Havelberg a Pietro il Venerabile: Federico Barbarossa e Baume-les-Messieurs. - Lees, Jay Terry (Benedictina, 1993)
Keywords: 👤 anselm of havelberg

Un religieux prémontré, voyageur et pèlerin: le bienheureux Tancrède, initiateur de l'abbaye de La Lucerne - Lelegard, Marcel (Les Prémontrés pèlerins, voyageurs et missionnaires ; Les abbayes des Ardennes françaises et belges : actes officiels du 18e Colloque du Centre d'études et de recherches prémontrées, 1993)
Keywords: la lucerne

Kościół z klasztorem Świętego Wincentego we Wrocławiu - Malachowicz, Edmund; Brzezowski, Wojciech (DTSK Silesia, 1993)
OCLC: 833991347
Keywords: wrocław

Strahov Praha: das Strahover Kloster in Prag - Maleček, František; Maleček, Roman (Nakl. Orion, 1993)
Pages: 149
Keywords: strahov

El monasterio de Santa María la Real (Aguilar de Campoo, Palencia) - Matesanz Vera, Pedro (Boletín de arqueología medieval, 1993)
Keywords: aguilar de campoo

Die Meerer Hofesgüter im ehemaligen Amt Lank – Der Hegerhof - Meyer-Rogmann, Vera (Meerbuscher Geschichtshefte, 1993)
Keywords: meer

Philip of Harvengt and Anselm of Havelberg: The Premonstratensian Vision of Time - Neel, Carol (Church History: Studies in Christianity and Culture, 1993)
Keywords: 👤 anselm of havelberg; 👤 philip of harvengt

Philip of Harvengt and Anselm of Havelberg: the Premonstratensian vision of time - Neel, Carol Leigh (Church history, 1993)
Keywords: 👤 anselm of havelberg; 👤 philip of harvengt

Pfarrkirche und Stiftskirche zu Leitzkau - Nickel, Heinrich Leopold (Deutscher Kunstverlag, 1993)
Keywords: leitzkau

Børglum, Tønsberg, Dragsmark - Nyberg, Tore (Seminaret "Kloster og by" 11.-13. november 1992: omkring Olavsklosteret, Premonstratenserordenen og klostervesenet i middelalderen, 1993)
OCLC: 467278997
Keywords: børglum; dragsmark; tønsberg

Saint-Jean-de-la-Castelle - Oberste, Jörg (Lexikon für Theologie und Kirche, 1993)
Keywords: la castelle

Saint-Just-en-Chaussée - Oberste, Jörg (Lexikon für Theologie und Kirche, 1993)
Keywords: saint-just-en-chaussée

850 let Strahovského kláštera. Jindřich Zdík a osazení Strahovského kláštera premonstráty - Pařez, Jan (Dějiny a současnost, Kulturně historická revue, 1993)
[850 Jahre Stift Strahov. Heinrich Zdík und die Gründung des Prämonstratenserstiftes Strahov]
Keywords: strahov

Die Geschichte des Klosters Wirberg - Passler, Karl-Heinz (Hessische Heimat (Gießen), 1993)
Keywords: wirberg

Das Aschaffenburger Psalterium der Gertrud von Altenberg und sein Ludowinger-Nekrolog - Petersohn, Jürgen (Alma mater Philippina, 1993)
Keywords: altenberg

Stiftsbibliothek Geras - Pfiffig, Ambros Josef (Geraser Hefte, 1993)
Keywords: geras

Schlägl und das obere Mühlviertel unter dem Passauer Bischof Otto von Lonsdorf (1254-1265) - Pichler, Isfried Hermann (Schlägl intern, 1993)
Keywords: schlägl

Notre-Dame et Saint-Nicolas d'Hermières - Plouvier, Martine (Dictionnaire d'histoire et de géographie ecclésiastiques, 1993)
Keywords: hermières

Znak Strahovského kláštera - Pokorný, Pavel R. (Heraldická ročenka, 1993)
[850 Jahre Kloster Strahov]
Keywords: strahov

Kafr Jinnis - Pringle, Denys (The Churches of the Crusader Kingdom of Jerusalem: A Corpus, 1993)
Keywords: st. habakuk

Rantis - Pringle, Denys (The Churches of the Crusader Kingdom of Jerusalem: A Corpus, 1993)
Keywords: st. joseph

Klasztor norbertanek na Zwierzyncu w. wiekach srednich - Rajman, Jerzy (Secesja, 1993)
Keywords: zwierzyniec

L'abbaye prémontrée de Bellelay (1140-1420), histoire socio-économique d'une abbaye prémontrée jurassienne (précédée d'une analyse archivistique et diplomatique) - Rebetez, Jean-Claude (Positions des thèses de l'École des Chartes, 1993)
Keywords: bellelay

L'abbaye prémontrée de Bellelay, 1140-1420, histoire socio-économique d'une abbaye prémontrée jurassienne, précédée d'une analyse archivistique et diplomatique - Rebetez, Jean-Claude (École nationale des chartes, 1993)
Keywords: bellelay

Der Kirchberg bei Niedergründau - Rückriegel, Erwin (Grindaha, 1993)
Keywords: niedergründau

Der Kirchberg bei Niedergründau: ein kurzer Führer - Rückriegel, Erwin (1993)
Keywords: niedergründau

Das Stift Tepl und die Prämonstratenser in Obermedlingen - Schmidt, Erhard; Vogt, Gilbert (Auer, 1993)
Pages: 183
Keywords: teplá

Die Hirsauer Reform und die Kirchenbauten Bischof Ottos I. für die Klöster Windberg, Biburg und Prüfening - Schwarzmann, Peter (850 Jahre Prämonstratenserabtei Windberg, 1993)
Keywords: windberg

Beauchief Abbey: notes on the layout and remains; the abbey and surrounding area - Smith, A.V. (Privately Printed, 1993)
Keywords: beauchief

El monasterio premonstratense de Santi Spiritus - Sobrino Chomón, Tomás (Cuadernos Abulenses, 1993)
Keywords: ávila

Archeologisch onderzoek tijdens de reconstructie van het Abdijplein in Middelburg - Van Heeringen, R.M. (Walacria, 1993)
Keywords: middelburg

Pozůstatky románského zastřešení kostela sv. Martina v Bernarticích - Varhaník, Jiří (Zprávy památkové péče, 1993)
Keywords: bernartice

Die Ausgrabungen 1990-91 im Prämonstratenserkloster Windberg, Lkr. Straubing-Bogen - Wojaczek, Christoph (Vorträge des 11. Niederbayerischen Archäologentages : Deggendorf : 24. bis 26. April 1992, 1993)
Keywords: windberg

Een opgraving heropgegraven: Norbertijnen in Ninove, prov. Oost-Vlaanderen: interimverslag - Wouters, Werner; Peersmann, Jaak (Archeologie in Vlaanderen, 1993)
Keywords: ninove